Trophic ecology of groundwater species reveals specialization in a low‐productivity environment. (24th June 2015) - Francois, Clémentine M.; Mermillod‐Blondin, Florian; Malard, Florian; Fourel, Francois; Lécuyer, Christophe; Douady, Christophe J.; Simon, Laurent
Summary: Identifying feeding strategies at lower bounds of habitat productivity is fundamental to understand the relationship between energy availability and trophic specialization. Low productivity is expected to severely constrain trophic specialization because organisms may no longer be able to fulfil their energy requirements by feeding on a reduced set of resources. However, species living in low‐productivity habitats often exhibit particular biological traits such as low metabolic rates and high food‐finding abilities, which may release constraints on trophic specialization. In the present study, we used carbon (C) and nitrogen (N) stable isotopes to measure the degree of trophic specialization in two species of isopods ( Proasellus valdensis and Proasellus cavaticus ) living in groundwater, one of the most energy‐limited environments on earth. Fundamental specialization was obtained from a 13 C/ 15 N‐labelling experiment in the laboratory: we measured separately the carbon and nitrogen assimilation rates of the two species across the three food sources encountered in their natural cave habitats (fine and coarse particulate organic matter and sedimentary biofilm). Then, for each species, we tested for variation in diet composition among individuals and populations by quantifying the relative contribution of the three food sources to the diet of multiple individuals within 5 cave populations. The labelling experiment showed that both species assimilated about 10 times more carbon and at least 4 times more nitrogen from sedimentary biofilm than from both forms of particulate organic matter. Field samplings showed that sedimentary biofilm made up, on average, 83% of the diet of isopods. Moreover, we found almost no variation in diet among individuals of a cave population as well as among cave populations within species. This study provides the first evidence of a high degree of trophic specialization in a low‐productivity cave environment. Both species exhibited a strong fundamental specialization on sedimentary biofilm and most probably fed selectively on this food source in their natural environment. Our findings challenge the prediction that species would adopt generalist feeding strategies at lower bounds of habitat productivity. Abstract : Lay Summary